The Style of Kināyah in the Qur'an: A Critical Analysis from the Perspective of Bayan of the Verses on Social Interaction - Sarmilah Amir; Mardan Mardan; Andi Miswar (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Human language often has limitations and can seem vulgar when articulating private domestic matters. This is where the Qur’an uniquely comes into play by utilizing the flexibility of uslūb kināyah (a figurative style of speech or subtle allusion) as an aesthetic and ethical linguistic instrument. This study aims to critically analyze the mechanisms of uslūb kināyah, including its meaning, components, classification, and significance by focusing specifically on verses regarding mu‘āsyarah (intimate spousal interaction). This is a descriptive qualitative study based on library research. Primary data is sourced from the mu‘āsyarah verses in the Qur’an, which are analyzed using a stylistic and exegetical approach through thematic study methods. The results of the study indicate that the semantic mechanism of uslūb kināyah operates through the interconnection of its three main elements, whereby the figurative meaning is conveyed profoundly without invalidating the original meaning according to sharia logic. In the mu‘āsyarah verses (such as QS. al-Baqarah: 187, 223, 235; QS. al-Nisā’: 21, 43; QS. al-A‘rāf: 189; and QS. al-Zukhruf: 18), the Qur’an consistently employs euphemism by shifting from explicit (ṣarīḥ) diction to suggestive expressions rich in aesthetic value. This is evidenced by the use of the word libās (clothing) to refer to intimacy, ḥarṡ (field) to refer to uterine reproduction, and the words lāmastum, tagasysyā, and afḍā to represent sexual intercourse. This study concludes that the uslūb kināyah in the mu‘āsyarah verses plays a strategic role in balancing the morality of polite speech (adab al-kalim) without obscuring or diminishing the precision of the fiqh legal rulings contained therein.